Multi-actor human rights protection at the International Criminal Court - Irving, Emma, 1989- (Cambridge (UK): Cambridge University Press, 2020)
"The International Criminal Court (ICC) was envisaged as a beacon of international criminal justice, but it cannot exist or operate in splendid isolation. Rather, it is inextricably linked to, and reliant on, the international community of States. Such reliance has long been a feature of international criminal justice: speaking of the International Criminal Tribunal for the Former Yugoslavia, Antonio Cassese once wrote that the Tribunal was 'like a giant without arms and legs'. The artificial limbs the Tribunal needed to walk and work were state authorities, whose cooperation was key to the Tribunal's functioning"--
The Human Rights Obligations of the ICC -- The Human Rights Obligations of States Parties to the Rome Statute -- Suspects, Accused, Convicted, and Acquitted -- Witnesses -- The Human Rights Obligations of the ICC Host State -- Accused, Convicted, and Acquitted -- Detained and Non-Detained Witnesses -- Evaluation and Proposals for Change -- Conclusion.
Includes bibliographical references and index.
Keywords: International Criminal Court; International Criminal Court; Human rights; Human Rights; Droits de l'homme (Droit international); Human rights